Measuring Women's Agency - Donald, Aletheia; Koolwal, Gayatri; Annan, Jeannie; Goldstein, Markus (Taylor and Francis, 2021)
Improving women’s agency, namely their ability to define goals and act on them, is crucial for advancing gender equality and the empowerment of women. Yet, existing frameworks for measuring women’s agency – both disorganized and partial – provide a fragmented understanding of the constraints women face in exercising their agency, thus restricting the design of reliable and valid interventions and evaluation of their impact. This paper proposes a multidisciplinary framework for capturing individual agency, containing three critical dimensions: goal setting, perceived control and ability to initiate action toward goals (“sense of agency”), and acting on goals. For each dimension, the paper reviews existing measurement approaches and what is known about their relative quality. The study concludes by highlighting that future research to improve the measurement of women’s agency should prioritize incorporating different contexts, age groups, and decision-making areas to ensure programming and policies are meaningful to the lives of women.